Is socially responsible production a normal good? - Jana Friedrichsen (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper uses a controlled laboratory experiment to investigate the effect of wealth on individual social responsibility (ISR), defined as choosing a more socially responsible product if a cheaper alternative is available. We find that rich consumers are significantly less likely to engage in ISR than poor consumers. This suggests that socially responsible production conditions may not be normal product attributes.
Keywords: M14; A13; C91; D03; 330; social responsibility; consumer behavior; market experiment; wealth effect